Bending the Arc of the Trilobed Flap Through External Interlobe Angle Inequality. Issue 5 (May 2018) - Wang, Chang Ye; Armbrecht, Eric S.; Burkemper, Nicole M.; Glaser, Dee Anna; Maher, Ian A.
Abstract : BACKGROUND: The trilobed flap is a useful repair option for distal nasal defects. In certain cases, however, the placement of its quaternary defect may risk compression of the internal nasal valve or induction of ectropion. In this study, we propose a modified design of the trilobed flap, which uses unequal external interlobe angles. OBJECTIVE: To present the design principles and results of our modified trilobed flap for the reconstruction of difficult distal nasal Mohs defects. MATERIALS AND METHODS: Mohs defects of 26 patients were reconstructed (21 with long-term follow-up) using our modified trilobed flap over 1 year. Two independent masked raters graded postoperative photographs for alar symmetry and overall cosmesis. RESULTS: Median alar symmetry scores were excellent and overall cosmesis grades were between excellent and very good. CONCLUSION: The modified trilobed flap with unequal external angles offers an excellent option for reconstruction of Mohs defect of the distal nose that may not be well-suited for other repairs. Over 1 year, 21 modified trilobed repairs were performed with overall excellent outcomes.